Can Tax Increment Financing Benefit U.S. Rust Belt Communities?. Issue 4 (November 2022) - Dzigbede, Komla D.; Pathak, Rahul
Place-based economic policies and value-capture instruments are resurging in many American communities looking for alternative ways to fund infrastructure projects and support local economic revival. Using principal component methods, the authors construct an index for identifying distressed neighborhoods to enable the targeting of place-based policies involving tax increment financing (TIF). In addition, the authors use the Monte Carlo method to simulate the impact of a TIF intervention on employment and property values in neighborhoods. The analysis focuses on Broome County in upstate New York, a region that witnessed massive deindustrialization as manufacturing firms moved to other states and overseas. The authors find that a significant fraction of neighborhoods in the study area would qualify for TIF-type policies that would lead to significant improvements in property values and, likely, modest employment effects.